DNA methylation profiles differ in responders versus non-responders to anti-PD-1 immune checkpoint inhibitors in patients with advanced and metastatic head and neck squamous cell carcinoma - Matthias Preusser; Anna Sophie Berghoff; Thorsten Fuereder; Leonhard Müllauer; Gerwin Heller; Angelika Martina Starzer; Katharina Feldmann; Erwin Tomasich; Teresa Hatziioannou; Stefan Traint; Thomas Melchardt; Christoph Minichsdorfer; et al. (Journal for ImmunoTherapy of Cancer)
Background Biomarkers for response prediction to anti-programmed cell death 1 (PD-1) immune checkpoint inhibitors (ICI) in patients with head and neck squamous cell carcinoma (HNSCC) are urgently needed for a personalized therapy approach. We investigated the predictive potential of inflammatory parameters and DNA methylation profiling in patients with HNSCC treated with anti-PD-1 ICI.Methods We identified patients with HNSCC that were treated with anti-PD-1 ICI therapy in the recurrent or metastatic setting after progression to platinum-based chemotherapy in two independent centers. We analyzed DNA methylation profiles of >850.000 CpG sites in tumor specimens of these patients by Infinium MethylationEPIC microarrays, immune cell density in the tumor microenvironment (CD8, CD3, CD45RO, forkhead box P3 (FOXP3), CD68), PD-1 and programmed cell death ligand 1 (PD-L1) expression by immunohistochemistry, and blood inflammation markers (platelet-to-lymphocyte ratio, leucocyte-to-lymphocyte ratio, monocyte-to-lymphocyte ratio, neutrophil-to-lymphocyte ratio). DNA methylation profiles and immunological markers were bioinformatically and statistically correlated with radiological response to anti-PD-1 ICI.Results 37 patients with HNSCC (median age of 62 years; range 49–83; 8 (21.6%) women, 29 (78.4%) men) were included (Center 1 N=26, 70.3%; Center 2 N=11, 29.7%). Median number of prior systemic therapies was 1 (range 1–4). Five out of 37 (13.5%) patients achieved an objective response to ICI. Median progression-free survival and median overall survival times were 3.7 months (range 0–22.9) and 9.0 months (range 0–38.8), respectively. Microarray analyses revealed a methylation signature including both hypomethylation and hypermethylation which was predictive for response to ICI and included several genes involved in cancer-related molecular pathways. Over-represented differentially methylated genes between responders and non-responders were associated with ‘Axon guidance’, ‘Hippo signaling’, ‘Pathways in cancer’ and ‘MAPK signaling’. A statistically significant correlation of PD-L1 expression and response was present (p=0.0498).Conclusions Our findings suggest that tumor DNA methylation profiling may be useful to predict response to ICI in patients with HNSCC.